A NEW VOICE IN ELT: PLANNING INTENSIVE WORKPLACE CURRICULUM - Amporn Sa-mgiamwibool (International Conference on Education and Language (ICEL), 2016)
The emergence of AEC and its consequences on English language teaching leads to three critical issues that involve ELT, ESL and EFL. In response to this, practitioners and teachers of the fields find it necessary to identify the language required in workplace. This paper describes one approach by means of survey to discover the necessary language functions in which they are used in the workplace and apply the language functions to draft a work-based curriculum. The results illustrated the general language functions necessary for: 1) a work topic; 2) work interaction; 3) appropriate usage for verbal communication; and 4) nonverbal communication. Practically, Master of Arts in English for Careers, a work-based curriculum, was drafted to serve the local, regional and global marketplaces.